PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS IV PADA PEMBELAJARAN IPAS MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA INTERAKTIF BAAMBOOZLE - Ihsan, Thoriq Ikhwanul; Media, Afriza; Fitria, Yanti; Fitri, Umiatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of fourth-grade students in Natural and Social Science (IPAS) learning at SDN 03 Patamuan, Padang Pariaman Regency, caused by teacher-centered instruction dominated by the lecture method, which left students passive, minimally engaged in critical thinking and problem solving, and low in interaction and learning motivation. This study aims to describe the planning, implementation, and learning outcomes of students in IPAS learning using the Problem Based Learning (PBL) model assisted by the Baamboozle interactive media. This research is a Classroom Action Research (CAR) using a qualitative and quantitative approach, conducted in two cycles (Cycle I with two meetings, Cycle II with one meeting) following the stages of planning, action, observation, and reflection. The research subjects were 24 fourth-grade students of SDN 03 Patamuan. Data were collected through observation sheets and evaluation tests. The results showed consistent improvement in every aspect: the lesson-plan (modul ajar) assessment increased from 79.17% to 95.83%; teacher activity from 82.14% to 92.86%; student activity from 82.14% to 92.86%; the affective aspect from 62.50 to 82.29; the psychomotor aspect from 59.03 to 87.85; and the cognitive aspect from 65.83 (41.7% reaching the learning-objective criterion) to 83.79 (83.3% reaching the criterion). It can be concluded that the application of the Problem Based Learning model assisted by the Baamboozle interactive media effectively improves fourth-grade students' learning outcomes in IPAS.